Privacy Violations in Live Streaming Pose Significant Legal Challenges Globally: Pelanggaran Privasi dalam Siaran Langsung Menimbulkan Tantangan Hukum yang Signifikan Secara Global - Jaya, Nur Intan Purwani; Multazam, Mochammad Tanzil (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The rise of social media has significantly transformed the landscape of personal fame and income generation, particularly with the advent of live streaming. Specific Background: However, this phenomenon has led to ethical concerns regarding privacy violations, where individuals are recorded without consent, potentially resulting in reputational harm. Privacy is a fundamental right, and its violation undermines the principles of human dignity and autonomy. Knowledge Gap: While existing literature discusses the implications of privacy in digital spaces, there is a limited exploration of legal frameworks that govern these practices, particularly in relation to live streaming platforms. Aims: This research employs a normative legal analysis, focusing on Indonesian regulations, to examine the legality of privacy violations in live streaming contexts and to assess the accountability of content creators and platforms. Results: The analysis reveals that current legislation, particularly Article 26 of Law Number 11 of 2008 on Electronic Information and Transactions, mandates consent for the use of personal data. Violators can face legal repercussions, including imprisonment and fines, under Article 45 of the same law. Novelty: This study contributes to the discourse on digital privacy by linking legal obligations to ethical practices in social media, emphasizing the need for awareness among content creators. Implications: The findings underscore the necessity for stringent adherence to privacy laws in live streaming to protect individual rights, suggesting that both users and platforms must uphold ethical standards to foster a safe online environment, thereby reinforcing the protection of human rights in the digital age. Highlights: Social Media: Boosts fame and income through live streaming. Consent Required: Personal data use demands owner’s permission by law. Privacy Matters: Content creators must respect individual privacy rights. Keywords: Privacy Violations, Live Streaming, Social Media, Legal Framework, Consent